2020
DOI: 10.1016/j.nicl.2020.102432
|View full text |Cite
|
Sign up to set email alerts
|

Neural primacy of the dorsolateral prefrontal cortex in patients with obsessive-compulsive disorder

Abstract: Highlights Medication-free OCD patients were recruited to explore the neural primacy of DLPFC. Three abnormal causal interactions related to DLPFC were identified in OCD patients. Directionality of interaction within and between neural networks is disrupted in OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“… 22 The previous investigation in OCD patients showed reduced functional connectivity in the right DLPFC and the right OFC, and activity in the right OFC had an inhibitory on the right DLPFC. 38 There have been previous studies on the left, right, and bilateral OFC, and the results are not consistent because of the different protocols used in treatment. 27 , 39–42 A double-blind cross-over study evaluated the efficacy of low-frequency rTMS over the right OFC with a double-cone coil in patients suffering from OCD.…”
Section: Discussionmentioning
confidence: 90%
“… 22 The previous investigation in OCD patients showed reduced functional connectivity in the right DLPFC and the right OFC, and activity in the right OFC had an inhibitory on the right DLPFC. 38 There have been previous studies on the left, right, and bilateral OFC, and the results are not consistent because of the different protocols used in treatment. 27 , 39–42 A double-blind cross-over study evaluated the efficacy of low-frequency rTMS over the right OFC with a double-cone coil in patients suffering from OCD.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study utilized rs-fMRI to investigate the neural prioritization of the DLPFC in sufferers of OCD. They discovered abnormalities in the DLPFC-right orbitofrontal cortex circuit, DLPFC-inferior temporal gyri circuit, and DLPFC cerebellar circuit, verifying neural circuit abnormalities in an OCD patient alternative model (58). Therefore, DLPFC damage related to TA may cause symptoms of OCD in patients.…”
Section: Discussionmentioning
confidence: 87%
“…In prior resting-state fMRI studies, altered connectivity regarding the DLPFC has been found in OCD patients relative to HCs, suggesting that the DLPFC might be central to OCD pathophysiology (11,49). A more recent rs-fMRI study using bivariate Granger causality analysis demonstrated the abnormal causal interactions of DLPFC-related circuits in patients with OCD (50). Our finding that greater activation in the DLPFC during the MR task was associated with severe obsessivecompulsive symptoms may be related to patients' efforts to resist their symptoms during cognitive tasks.…”
Section: Discussionmentioning
confidence: 98%